DIAGNÓSTICO DEL CLIMA ORGANIZACIONAL DEL PERSONAL DEL HOSPITAL LUIS MOSCOSO ZAMBRANO DEL CANTON PIÑAS, PERIODO 2017 - Ríos Lalangui, Diana Elizabeth (2019)
The present research work was carried out according to the parameters and guidelines of the National University of Loja and the Public Administration Career. The Organizational Climate is an important managerial function, whose results depend to a large extent on the success or failure of the functions. It means then an arduous struggle against all the factors that can exert their negative or positive influence on each member; there lies the importance of making a Diagnosis of the Organizational Climate of the Luis Moscoso Zambrano Hospital of the Piñas Canton, during the 2017 period. In order to carry out the Organizational Climate Diagnosis, it was necessary to raise specific aspects such as identifying the dimensions that influence the organizational climate, as well as determining the effect that the organizational climate has on the work performance, which was carried out through the application of surveys of employees and workers, and interviews were also conducted with the directors of the institution. Thus, it is considered that the Hospital Luis Moscoso Zambrano has a satisfactory Organizational Climate, taking into account that the dimensions studied are positively perceived by each of the employees and workers, highlighting among them the reward and identity, it is also verified that the they affect the work performance of the staff positively; and it is established that thanks to the positive perception of the dimensions, the institution achieves the fulfillment of the objectives and goals of each unit and of the institution.